Intellectual property rights and economic growth - Lindroos, Juho (2015)
Striving for greater economic growth, requires a great understanding of the underlying factors. One of the factors may be the intellectual property rights and the level of its protection. Whether it is and how does it behave are the questions answered by this thesis. The theoretical framework comes mainly from the Schumpeterian growth model. The empirical methodology uses GMM in order to obtain reliable results. The level of intellectual property rights protection in the country does seem to have a positive effect on the country’s growth rate. Furthermore it seems that the relation is non-linear: The incremental changes are different between low and high starting levels of the IPR protection.